Diving into people’s understanding of the deep sea: A comparative study from the east to the west of the Atlantic - Morais, C.; Teresa, A.; Atkinson, L.; Moreira, L.; Teixeira, A. S.; Rosa, M. (International Journal of Science Education Part B-Communication and Public Engagement, 2026)
During the Decade of Ocean Science, oceans and the deep sea have gained attention for their vital ecological roles, prompting increased scientific investment. However, this growing body of research has not effectively reached the public, especially regarding deep-sea ecosystems. Public perception studies are limited, particularly those focused on the deep sea. This article compares findings from a U.S. study with previous research in Portugal on social representations of the deep sea. A total of 521 U.S. participants completed tasks assessing representations, perceptions, and attitudes. Results mirror the Portuguese study, revealing vague and conflicting representations. Both populations use contrasting terms (known vs. unknown, literal vs. abstract) to describe the deep sea. Despite cultural differences, similar results emerge: the deep sea is linked to education, science, and climate, while perceived threats reflect current concerns. Attitudes are generally positive toward preservation, economic use, and scientific exploration, contrasting earlier findings that showed skepticism toward economic exploitation. This study highlights the value of cross-cultural comparisons in understanding public views on complex environmental topics and supports the need for tailored communication strategies.